Beban Kerja Dan Kebutuhan Berprestasi: Manakah Yang Penting Dalam Peningkatan Kinerja Pegawai? - Djaya , Subhan; Sjahruddin, Herman; Nasir, Nurjannah; Heslina, Heslina (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Performance is a result used by an organization to improve employee performance which originates from the results of employee work implementation as a form of their accountability to the organization where they work. This study aims to test whether workload and need for achievement can influence work results. The total population in this study was 114 employees. The sample used in this research was 53 respondents with the sample collection technique carried out through simple random sampling using a questionnaire. The results of regression testing using SPSS show that workload has a significant effect on employee performance, this condition is different from the need for achievement, which shows that the need for achievement does not contribute to performance achievement.